Addressing mental health in university students: a call for action - Li, Qiang; Li, Jiayi; Fan, Yisheng (Frontiers in Public Health, 2025)
Mental health has been a growing concern in universities worldwide, with an increasing number of students experiencing psychological problems impacting their academic and personal performance. The transition to university life is often accompanied by an increase in stress, including the need for independence, academic pressure, and social adjustment. For many students, this period can exacerbate pre-existing mental health conditions or trigger new struggles. This perspective mainly focuses on the vital part of mental health in education, and calls for the indispensable role that universities should play in supporting their students’ psychological well-being and integrating mental health education into the academic environment. The future of mental health in universities lies in continued innovation, collaboration, and dedication to ensuring that every student has access to the resources they need to thrive academically and personally.